Opposing cardiac effects of autoantibody activation of beta-adrenergic and M2 muscarinic receptors in cardiac-related diseases - Stavrakis, Stavros (2010)
BACKGROUND: Activating autoantibodies to β-adrenergic receptors (AAβ1/2AR) and M2 muscarinic receptors (AAM2R) have been reported in several cardiac diseases and may have pathophysiologic relevance. However, the interactions and relative effects of AAβ1AR, AAβ2AR and AAM2R on contractile function have not been characterized. METHODS: The inotropic effects of IgG from 18 selected patients with cardiomyopathy and/or atrial tachyarrhythmias positive by ELISA for antibodies to β1/2AR were studied using an isolated canine Purkinje fiber contractility assay. M2R-blockade was tested using atropine while selective β1AR and β2AR blockade used CGP-20712A and ICI-118551 respectively. RESULTS: Fifteen of the 18 anti-β1/2AR ELISA-positive samples demonstrated evidence for negative inotropic muscarinic effects which were blocked using atropine. Atropine failed to uncover a positive inotropic response in 2 of the 18 IgG samples (false positive ELISA for AAβAR). In the remaining 16 AAβAR true-positive subjects, the β1AR-induced increase in contractility (concurrent M2/β2 blockade) was augmented to 140.5 ± 12.2% of baseline compared to 127.4 ± 7.2% of baseline with M2 blockade (atropine) only (p<0.001, n = 16). The β2AR-induced increase in contractility (concurrent M2/β1 blockade) was only 114.5 ± 4.3% of baseline (p<0.001, n = 16). Combined M2 and β1/β2 blockade eliminated any increase in contractility. CONCLUSIONS: The inherently positive inotropic effect of AAβ1AR was negatively modulated by AAM2R and AAβ2AR. These opposing effects of receptor-activating autoantibodies may alter cardiac performance and influence clinical outcome depending on their receptor type and relative contractile activity.